2017
DOI: 10.1002/14651858.cd004953.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Sustained versus standard inflations during neonatal resuscitation to prevent mortality and improve respiratory outcomes

Abstract: Background At birth, infants' lungs are fluid-filled; this fluid must be replaced by air to allow for effective breathing. Some infants are judged to have inadequate breathing at birth and are resuscitated with positive pressure ventilation (PPV). Giving prolonged (sustained) inflations at the start of PPV may help clear lung fluid and establish gas volume in the lungs. Objectives To assess the efficacy of initial sustained (> one second duration) lung inflation compared to standard inflations (≤ one second) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Four RCTs showed no benefits at all [29,30,20,31]. However, according to the meta-analysis of Bruschettini et al [10], a decreased duration of MV was found (mean difference: -5.37 days; 95% CI: -6.31 to -4.43), but without differences in the rate of BPD nor combined mortality/BPD. Whether our positive results could be explained only by the adjunction of the possibly more protective dynamic PEEP LR manoeuver [32] should be addressed in a specific RCT.…”
Section: Discussionmentioning
confidence: 93%
“…Four RCTs showed no benefits at all [29,30,20,31]. However, according to the meta-analysis of Bruschettini et al [10], a decreased duration of MV was found (mean difference: -5.37 days; 95% CI: -6.31 to -4.43), but without differences in the rate of BPD nor combined mortality/BPD. Whether our positive results could be explained only by the adjunction of the possibly more protective dynamic PEEP LR manoeuver [32] should be addressed in a specific RCT.…”
Section: Discussionmentioning
confidence: 93%
“…Four RCTs showed no benefits at all [20,[29][30][31]. However, according to the meta-analysis of Bruschettini et al [10], a decreased duration of MV was found (mean difference: − 5.37 days; 95% CI: − 6.31 to − 4.43), but without differences in the rate of BPD nor combined mortality/BPD. Whether our positive results could be explained only by the adjunction of the possibly more protective dynamic PEEP LR manoeuver [32] should be addressed in a specific RCT.…”
Section: Discussionmentioning
confidence: 93%
“…Lung recruitment (LR) at birth using SI of 15-20 s was assessed in numerous randomized controlled trials (RCTs) summarized in 2 recent meta-analyses [10,11]. Despite encouraging results such as a reduced need for intubation, no benefit was found for reduction of mortality or bronchopulmonary dysplasia (BPD).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the lambs that received sustained inflations had greater and more homogenous lung aeration, differences were only significant for the first 3 hours of life. This may help to explain why although sustained inflations may reduce the need for ventilation, benefits do not appear to be sustained in the long term [4, 5].…”
Section: Prematurity and Lung Diseasementioning
confidence: 99%